2001
DOI: 10.1554/0014-3820(2001)055[0994:fralsb]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Females Receive a Life-Span Benefit From Male Ejaculates in a Field Cricket

Abstract: Mating has been found to be costly for females of some species because of toxic products that males transfer to females in their seminal fluid. Such mating costs seem paradoxical, particularly for species in which females mate more frequently than is necessary to fertilize their eggs. Indeed, some studies suggest that females may benefit from mating more frequently. The effect of male ejaculates on female life span and lifetime fecundity was experimentally tested in the variable field cricket, Gryllus lineatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(52 citation statements)
references
References 48 publications
2
49
1
Order By: Relevance
“…Males do not produce a nutritious spermatophylax, and the spermatophore is small, weighing, on average, about 0.66% of body mass (Evans 1988). Although Wagner et al (2001) found that repeated mating increased fecundity in another field cricket with small spermatophores, comparison of female T. commodus experimentally assigned either one or three matings with a single male revealed no difference in lifetime fecundity or egg hatching success (M. D. Jennions, J. Hunt, and R. C. Brooks, unpubl.…”
Section: Study Speciesmentioning
confidence: 99%
“…Males do not produce a nutritious spermatophylax, and the spermatophore is small, weighing, on average, about 0.66% of body mass (Evans 1988). Although Wagner et al (2001) found that repeated mating increased fecundity in another field cricket with small spermatophores, comparison of female T. commodus experimentally assigned either one or three matings with a single male revealed no difference in lifetime fecundity or egg hatching success (M. D. Jennions, J. Hunt, and R. C. Brooks, unpubl.…”
Section: Study Speciesmentioning
confidence: 99%
“…Responses to each treatment are described as the effect of multiple mating relative to the control: NA -trait not assayed, ↑ -trait value increased, ↓ -trait value decreased, X -no effect of treatment. (Fedorka and Zuk, 2005); [3] (Wagner et al, 2001);[4] (Ivy and Sakaluk, 2005); [5] (Burpee and Sakaluk, 1993), [6] (Gershman, 2010);[7] (Gershman, 2007). * this study conducted principal component analysis (PCA) and so PCA values have been associated with the most appropriate fitness trait, † in this study, diet was manipulated but we present data for animals fed ad libitum.…”
mentioning
confidence: 99%
“…In Teleogryllus commodus, egg-laying activity was stimulated by prostaglandin injections and oviposition increase was a function of prostaglandin quantity (StanleySamuelson et al 1986). Laupala ejaculate may also contain beneficial substances as found in Gryllus lineaticeps, where repeated mating has been demonstrated to significantly lengthen female lifespan and as a result increase lifetime fecundity (Wagner et al 2001). Alternatively, it could just be the copulatory action that is important, rather than the reception of microspermatophores by females.…”
Section: Discussionmentioning
confidence: 99%